2021
DOI: 10.3389/fendo.2021.708216
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Free Triiodothyronine to Free Thyroxine Ratio in Euthyroid Patients With Myocardial Infarction With Nonobstructive Coronary Arteries

Abstract: BackgroundThyroid function is closely involved in cardiovascular diseases. The free triiodothyronine (fT3) to free thyroxine (fT4) ratio has been reported as a risk factor for coronary artery disease, but its prognostic value in euthyroid patients with myocardial infarction with nonobstructive coronary arteries (MINOCA) remains unclear.MethodsA total of 1162 euthyroid patients with MINOCA were enrolled and divided according to decreased tertiles of fT3/fT4 ratio. The study endpoint was major adverse cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Regarding fT4, higher levels (cut-off 12.54 pg/mL) were associated with worse outcome compared to lower levels [ 67 ]. The fT3/fT4 ratio was also shown to be associated with worse outcomes in patients diagnosed with MI with nonobstructive coronary arteries ( n = 1162) over a median follow-up of 41.7 months [ 68 ]. Patients were divided into three groups based on fT3/fT4 tertiles: tertile 1 ≥ 2.64 ( n = 387), tertile 2 2.28–2.63 ( n = 386), and tertile 3 < 2.28 ( n = 389).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding fT4, higher levels (cut-off 12.54 pg/mL) were associated with worse outcome compared to lower levels [ 67 ]. The fT3/fT4 ratio was also shown to be associated with worse outcomes in patients diagnosed with MI with nonobstructive coronary arteries ( n = 1162) over a median follow-up of 41.7 months [ 68 ]. Patients were divided into three groups based on fT3/fT4 tertiles: tertile 1 ≥ 2.64 ( n = 387), tertile 2 2.28–2.63 ( n = 386), and tertile 3 < 2.28 ( n = 389).…”
Section: Resultsmentioning
confidence: 99%
“…Patients were divided into three groups based on fT3/fT4 tertiles: tertile 1 ≥ 2.64 ( n = 387), tertile 2 2.28–2.63 ( n = 386), and tertile 3 < 2.28 ( n = 389). Patients with lower fT3/fT4 had a higher incidence of MACE (all-cause death, nonfatal MI, revascularization, nonfatal stroke, and hospitalization for unstable angina or HF) (10%, 13.9%, and 18.2%; p = 0.005) and composite endpoint of death, reinfarction, revascularization, or stroke (5.4%, 8.5%, and 11.5%; p = 0.035) [ 68 ]. Compared to higher fT3/fT4 (tertile 1), lower fT3/fT4 was associated with an increased risk of MACE.…”
Section: Resultsmentioning
confidence: 99%
“…et al. found that a lower level of FT3/fT4 ratio remained a robust predictor of MACE in euthyroid MINOCA patients ( 29 ). When we focus on non-cardiac disease studies, high levels of FT4/FT4 ratio still represent the worsening illness condition.…”
Section: Discussionmentioning
confidence: 99%
“…FT3/FT4 reaction 5’-deiodinase activity can be used to evaluate peripheral thyroid sensitivity ( 2 , 11 14 ). The FT3/FT4 ratio seems to be a precise and reasonable indicator of thyroid hormone metabolic change that is associated with the prognosis of specific diseases, including coronary heart disease (CHD), myocardial infarction (MI), and dilated cardiomyopathy (DCM) ( 15 18 ). However, there are no data on the value of the FT3/FT4 ratio in predicting mortality risk in the general population, especially in those with normal thyroid function.…”
Section: Introductionmentioning
confidence: 99%